The empirical analysis of human capital competences on the example of company executives - Drozdowski, Grzegorz (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: Diagnosing the competences of human capital is a complex process, involving many approaches and steps leading to the recognition of the entire problem situations of the organization and its employees. Due to the increasingly higher and ever-growing position of the human capital formation system in the overall process of managing an organization, the analysis and diagnosis of management competencies is a process of particular importance. In the era of the knowledge-based economy, employee competencies are the key to competitive advantage. An important issue, therefore, is the constant monitoring of managers attitudes to improve their competences and conducting a systematic analysis of their component structure. Aim: This article aims objective of developing a factor structure of the rational dimension of management competencies based on knowledge, skills, and comprehension. Due to this objective, the factor structure of the knowledge and skills that managers have was determined. The practical level of self-assessment of the rational components of competence from the point of view of the influence of situational factors was also determined. Results: A questionnaire, an interview and literature studies were used for the research carried out in 2019–2020. The questionnaire was addressed to 282 employees of enterprises in the Lubusz Voivodeship of Poland. This allowed determining the degree of managers determination expressed in the need to adjust the competence potential they have to changeable situational factors.